2009
DOI: 10.1038/aps.2009.50
|View full text |Cite
|
Sign up to set email alerts
|

Are isothiocyanates potential anti-cancer drugs?

Abstract: Isothiocyanates are naturally occurring small molecules that are formed from glucosinolate precursors of cruciferous vegetables. Many isothiocyanates, both natural and synthetic, display anticarcinogenic activity because they reduce activation of carcinogens and increase their detoxification. Recent studies show that they exhibit anti-tumor activity by affecting multiple pathways including apoptosis, MAPK signaling, oxidative stress, and cell cycle progression. This review summarizes the current knowledge on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
183
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(191 citation statements)
references
References 53 publications
4
183
0
4
Order By: Relevance
“…Numerous studies have also reported that BITC inhibits many other types of cancer cell growth, such as breast cancer [11] , prostate cancer [12] , and glioma [20] . Although mechanistic studies have shown that the anticarcinogenic activity of BITC may be due to the induction of apoptosis or cell cycle arrest, increased oxidative stress, or interference with cell survival signaling pathways, the precise underlying mechanism is not fully understood [9] . The present study provides the first evidence of autophagy induction by BITC in human lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have also reported that BITC inhibits many other types of cancer cell growth, such as breast cancer [11] , prostate cancer [12] , and glioma [20] . Although mechanistic studies have shown that the anticarcinogenic activity of BITC may be due to the induction of apoptosis or cell cycle arrest, increased oxidative stress, or interference with cell survival signaling pathways, the precise underlying mechanism is not fully understood [9] . The present study provides the first evidence of autophagy induction by BITC in human lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some isothiocyanates, such as allyl isothiocyanate (AITC), benzyl isothiocyanate (BITC), phenethyl isothiocyanate (PEITC) and sulforaphane (SFN), have been shown to have substantial chemopreventive activity against various human malignancies [7] . The mechanism of the isothiocyanate chemopreventive activity is thought to be associated with the inhibition of the metabolic activation of carcinogens by phase I enzymes (cytochrome P450 isozymes), and the increased excretion of carcinogens by inducing increased activities of phase II enzymes (quinone reductase and GSH S-trans ferases) [8,9] . Numerous studies have also demonstrated the anticancer effects of isothiocyanates in various cancer types, such as leukemia [10] , breast cancer [11] , prostate cancer [12] and lung cancer [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure compounds of these three groups have been extensively researched in vivo and in vitro studies on many types of cell lines for their potential effects in cancer treatment and prevention. These bioactive compounds act via multiple mechanisms such as cancer cell signalling, proliferation, apoptosis, migration, invasion, as well as angiogenesis and carcinogen elimination [51,52,53,54,55,56,57,58] to exhibit in vitro and in vivo anticancer activities.…”
Section: Pinnamaneni World Journal Of Pharmacy and Pharmaceutical Scmentioning
confidence: 99%
“…3.2.1.147), is physically separated from its substrate glucosinolates, yet may be present in the same cells and tissues 2. When plants containing glucosinolates are subjected to mechanical disruption, myrosinase comes into contact with the glucosinolates and, depending on substrate chemistry, pH, presence of Fe 2+ ions, and presence of countervailing enzymes such as epithiospecifier protein, converts them into either ITCs, thiocyanates, or nitriles 3. In animals, the conversion of dietary glucosinolates to ITCs is also carried out by the gastrointestinal microflora 4…”
Section: Introductionmentioning
confidence: 99%